Pengaruh Penggunaan E-Commerce Bagi Pengembangan Usaha Kecil Menengah (Ukm) Dengan Pendekatan Technology Acceptance Model - Ibnu Dwi Lesmono - AMIK BSI Purwokerto (Evolusi : Jurnal Sains dan Manajemen, 2015)
Abstract   In the current era of globalization, the SME sector is required to be able to compete in the market their business. Empowerment of Small and Medium Enterprises (SMEs) to be very strategic, because great potential in moving economic activities, and at the same time become the foundation source of income most people to improve their welfare. SMEs are required to make changes in order to increase their competitiveness. One way to compete in the competition in this era of globalization is to utilize information technology in the form of Internet media Internet provides many advantages for businesses, such as the capability of reaching a new segment, which can sell products not only for the local market, but also for the global market . One form of information technology that can be applied by the Small and Medium Enterprises (SMEs) to expand its business is to maximize the use of e-commerce.   Keywords: Business, E-Commerce, Internet.